Histoplasmosis on bone marrow aspirate smears associated with hemophagocytosis in a patient with Tuberculosis (Indian Journal of Case Reports, 2019)
Histoplasmosis infection causes spectrum of illness ranging from transient respiratory infections to disseminated disease. It is caused by a dimorphic fungus Histoplasma capsulatum [1-3] and the mode of infection is through inhalation of its spores. The disseminated histoplasmosis is not common and can present as acute, subacute or chronic illness [2-4]. The acute form is fatal and usually seen in immunocompromised individuals while the chronic form has an indolent course.